Effects of health-system strengthening on under-5, infant, and neonatal mortality: 11-year provincial-level time-series analyses in Mozambique - Quinhas F Fernandes, MPH; Bradley H Wagenaar, MPH; Laura Anselmi, MPhil; James Pfeiffer, PhD; Stephen Gloyd, MD; Kenneth Sherr, PhD (Elsevier, 2014)
Background: Knowledge of the relation between health-system factors and child mortality could help to inform health policy in low-income and middle-income countries. We aimed to quantify modifiable health-system factors and their relation with provincial-level heterogeneity in under-5, infant, and neonatal mortality over time in Mozambique. Methods: Using Demographic and Health Survey (2003 and 2011) and Multiple Indicator Cluster Survey (2008) data, we generated provincial-level time-series of child mortality in under-5 (ages 0-4 years), infant (younger than 1 year), and neonatal (younger than 1 month) age groups for 2000-10. We built negative binomial mixed models to examine health-system factors associated with changes in child mortality. Findings: Under-5 mortality rate was heterogeneous across provinces, with yearly decreases ranging from 11·1% (Nampula) to 1·9% (Maputo Province). Heterogeneity was greater for neonatal mortality rate, with only seven of 11 provinces showing significant yearly decreases, ranging from 13·6% (Nampula) to 4·2% (Zambezia). Health workforce density (adjusted rate ratio 0·94, 95% CI 0·90-0·98) and maternal and child health nurse density (0·96, 0·92-0·99) were both associated with reduced under-5 mortality rate, as were institutional birth coverage (0·94, 0·90-0·98) and government financing per head (0·80, 0·65-0·98). Higher population per health facility was associated with increased under-5 mortality rate (1·14, 1·02-1·28). Neonatal mortality rate was most strongly associated with institutional birth attendance, maternal and child nurse density, and overall health workforce density. Infant mortality rate was most strongly associated with institutional birth attendance and population per health facility. Interpretation: The large decreases in child mortality seen in Mozambique between 2000 and 2010 could have been partly caused by improvements in the public-sector health workforce, institutional birth coverage, and government health financing. Increased attention should be paid to service availability, because population per health facility is increasing across Mozambique and is associated with increased under-5 mortality. Investments in health information systems and new methods to track potentially increasing subnational health disparities are urgently needed. Funding: Doris Duke Charitable Foundation and Mozambican National Institute of Health.